2020
DOI: 10.1097/meg.0000000000002000
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical characteristics of early-onset colorectal cancer vs. late-onset colorectal cancer: a case-case study

Abstract: Background and objectives Early-onset colorectal cancer (eoCRC), defined as colorectal cancer (CRC) before the age of 50 is increasing in incidence. We evaluated exogenous and endogenous risk factors, and clinical features of eoCRC, compared to late-onset CRC (loCRC). Methods In this retrospective case-case study, patients were prospectively enrolled from 2015 to 2018. We collected clinical features (age, sex, time from symptom onset to diagnosis, sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 35 publications
4
34
1
Order By: Relevance
“…A total of 375 eoHRAs were found during colonoscopy surveillance, with the highest quintile of Western diet consumption as eoHRA risk factor (OR 1.67) and the highest quintile of prudent diet as a protective factor (OR 0.69) (Figure 2). Moreover, the Western diet was associated with advanced adenomas of the distal colon and rectum (OR 1.65), consistent with the typical eoCRC localization in the left colon and rectum [10,11]. These two dietary patterns have been described as exogenous factors associated with the prevention or predisposition of loCRC, too: respectively, the 'healthy' pattern (high in fruits, vegetables, and whole grains or legumes, fish, and low-fat milk or dairy products) and the 'unhealthy' or 'Western dietary' pattern (high in red and processed meat, sugary drinks, refined grains, desserts) [60].…”
Section: Foods and Eocrcsupporting
confidence: 70%
See 1 more Smart Citation
“…A total of 375 eoHRAs were found during colonoscopy surveillance, with the highest quintile of Western diet consumption as eoHRA risk factor (OR 1.67) and the highest quintile of prudent diet as a protective factor (OR 0.69) (Figure 2). Moreover, the Western diet was associated with advanced adenomas of the distal colon and rectum (OR 1.65), consistent with the typical eoCRC localization in the left colon and rectum [10,11]. These two dietary patterns have been described as exogenous factors associated with the prevention or predisposition of loCRC, too: respectively, the 'healthy' pattern (high in fruits, vegetables, and whole grains or legumes, fish, and low-fat milk or dairy products) and the 'unhealthy' or 'Western dietary' pattern (high in red and processed meat, sugary drinks, refined grains, desserts) [60].…”
Section: Foods and Eocrcsupporting
confidence: 70%
“…eoCRC has a distinct epidemiology, anatomical localization, histopathology, and clinical presentation compared to loCRC [ 9 ]. eoCRCs are typically located in the left colon (rectum, sigmoid colon, and descending colon) [ 10 , 11 ] and present more frequently at stage III–IV upon first diagnosis. They also tend to display a higher percentage of signet ring and mucinous histology as well as poor differentiation [ 2 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zisman et al observed that smokers were on average 5.2 years (95% CI: 4.9-5.5. years) younger at their colorectal cancer diagnosis than non-smokers. Two studies have investigated smoking as a driver for early-onset colorectal cancer [10,31]. While one study did not observe differences in smoking behavior, a more recent study supports our findings of early-onset patients being less likely to be smokers [10,31].…”
Section: Discussionsupporting
confidence: 80%
“…Two studies have investigated smoking as a driver for early-onset colorectal cancer [10,31]. While one study did not observe differences in smoking behavior, a more recent study supports our findings of early-onset patients being less likely to be smokers [10,31]. Taken together, our results suggest that the traditional risk factors for CRC such as BMI and smoking may not explain the recent increase in early-onset cancers, demonstrating the need to identify other risk factors that may explain this increasing trend of early-onset cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset CRC has attracted increasing attention from researchers in recent years, and reports from different regions around the world confirmed that the proportion of early-onset CRC is continuing to rise ( 34 38 ). Patients with early-onset CRC have a longer delay from symptom onset to diagnosis and are diagnosed at a higher rate of advanced stages than older patients ( 39 , 40 ). CRC is relatively slow to develop, and aggressive screening may reduce the incidence and allow for diagnosis before it progresses to an incurable stage, thereby reducing mortality and prolonging life ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%